Word signs : a first book of sign language - Slier, Debby (Washington, D.C. : Kendall Green Publications, 1995)
Provides words, illustrations, and sign language for common objects.
Cover title.
On board pages.
Originally published: New York : Checkerboard Press, c1993.
Keywords: Sign language -- Juvenile literature; Sign language; Vocabulary -- Juvenile literature; Vocabulary